Western diet‐induced increase in colonic bile acids compromises epithelial barrier in nonalcoholic steatohepatitis. Issue 5 (10th April 2020) - Gupta, Biki; Liu, Yunshan; Chopyk, Daniel M.; Rai, Ravi P.; Desai, Chirayu; Kumar, Pradeep; Farris, Alton B.; Nusrat, Asma; Parkos, Charles A.; Anania, Frank A.; Raeman, Reben
Abstract: There is compelling evidence implicating intestinal permeability in the pathogenesis of nonalcoholic steatohepatitis (NASH), but the underlying mechanisms remain poorly understood. Here we examined the role of bile acids (BA) in western diet (WD)‐induced loss of colonic epithelial barrier (CEB) function in mice with a genetic impairment in intestinal epithelial barrier function, junctional adhesion molecule A knockout mice, F11r −/− . WD‐fed knockout mice developed severe NASH, which was associated with increased BA concentration in the cecum and loss of CEB function. Analysis of cecal BA composition revealed selective increases in primary unconjugated BAs in the WD‐fed mice, which correlated with increased abundance of microbial taxa linked to BA metabolism. In vitro permeability assays revealed that chenodeoxycholic acid (CDCA), which was elevated in the cecum of WD‐fed mice, increased paracellular permeability, while the BA‐binding resin sevelamer hydrochloride protected against CDCA‐induced loss of barrier function. Sequestration of intestinal BAs by in vivo delivery of sevelamer to WD‐fed knockout mice attenuated colonic mucosal inflammation and improved CEB. Sevelamer also reduced hepatic inflammation and fibrosis, and improved metabolic derangements associated with NASH. Collectively, these findings highlight a hitherto unappreciated role for BAs in WD‐induced impairment of the intestinal epithelial barrier in NASH.